Diagnosis and Management of Post Traumatic Recurrent Unilateral Accommodative Spasm—A Case Report. Issue 3 (3rd July 2022) - Kumar P, Praveen; Bhowmick, Amit; Mahabale, Neha; Hussaindeen, Jameel Rizwana; Ratra, Dhanashree
ABSTRACT: Spasm of accommodation refers to constant contraction of the ciliary muscles of the eye, which fail to relax. Neurological issues, head injury, and psychogenic factors can lead to spasm of accommodation, which is generally bilateral. This case report describes the clinical presentation of traumatic, unilateral accommodative spasm in an army person. A 26-year-old male presented with complaints of diminution of near vision in the left eye noticed accidentally. History revealed a blunt injury in the eyebrow region of the left eye two months back. His best corrected visual acuity was 6/6, 0.8 M (N6) in the right eye and 6/9, 2.5 M (N18) in the left eye. Accommodative response was documented using an open-field autorefractometer that showed asymmetry in the accommodation response and pupillary diameter between the two eyes. One percent Atropine sulfate eye ointment – twice a day for 3 days – was prescribed. On the fourth day, the spasm was resolved in the left eye. Pre- and post-Atropine administration, lens thickness measurements were documented, which showed significant changes. Accommodative facility exercise was initiated after the pharmacological management. Unilateral accommodative spasm is rare and needs careful investigations. Objective assessment of accommodative response and lens thickness measurement play a vital role in confirming the diagnosis.